The sum of series $(2^2-1)(6^2-1)+(4^2-1)(8^2-1)+\cdots \cdots +\cdots (100^2-1)(104^2-1)$

Attempt Assume $\displaystyle S = \sum^{50}_{r=1}((2r)^2-1)((2r+4)^2-1) = \sum^{50}_{r=1}(4r^2-1)(4r^2+16r+15)$

$\displaystyle S = \sum^{50}_{r=1}(16r^4+64r^3+56r^2-16r-15)$

could some help me how to solve it, thanks

  • 1
    $\begingroup$ The sums $\sum_{r = 1}^{50}r, \sum_{r = 1}^{50}r^2, \sum_{r = 1}^{50}r^3$ and $ \sum_{r = 1}^{50}r^4$ may be solved separately. $\endgroup$ – Arthur Jan 16 '17 at 6:55
  • $\begingroup$ @Arther how i solve $\sum^{50}_{r=1}r^4,$ please explain me $\endgroup$ – DXT Jan 16 '17 at 6:56
  • $\begingroup$ I googled and found this, which looks like it might be helpful. $\endgroup$ – Arthur Jan 16 '17 at 6:58

You can find the sum using the idea of telescoping sum.

Since $$((2r)^2-1)((2r+4)^2-1)=(2r-1)(2r+1)(2r+3)(2r+5)$$ we get $$\small\begin{align}&\sum_{r=1}^{50}(2r-1)(2r+1)(2r+3)(2r+5)\\\\&=\frac{1}{10}\sum_{r=1}^{50}\color{red}{10}(2r-1)(2r+1)(2r+3)(2r+5)\\\\&=\frac{1}{10}\sum_{r=1}^{50}\color{red}{((2r+7)-(2r-3))}(2r-1)(2r+1)(2r+3)(2r+5)\\\\&=\frac{1}{10}\sum_{r=1}^{50}((2r+7)(2r+5)(2r+3)(2r+1)(2r-1)-(2r+5)(2r+3)(2r+1)(2r-1)(2r-3))\\\\&=\frac{1}{10}(107\cdot 105\cdot 103\cdot 101\cdot 99-7\cdot 5\cdot 3\cdot 1\cdot (-1))\end{align}$$

| cite | improve this answer | |

Being lazy, we could use the classical sums of powers of integer numbers as given here. This would lead to

$$ S_n = \sum^{n}_{r=1}(16r^4+64r^3+56r^2-16r-15)=\frac{1}{5} \left(16 n^5+120 n^4+280 n^3+180 n^2-71 n\right)$$

For sure, much more elegant is mathlove's solution.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.